Science, nation state, and democracy: Reimagining concepts - Visvanathan, Shiv and Parmar, Chandrika (Economic and Political Weekly)
In an attempt to go beyond the formal ideas of democracy, especially the much-vouched frameworks of electoral-ism, new lifeworlds of democracy are reimagined.- Reproduced